A Commentary on “Association Between Oral Behaviors and Painful Temporomandibular Disorders: A Cross-Sectional Study in the General Population” [Letter] - Fang J; Wu Y; Tong H (Journal of Pain Research)
Junhao Fang,1,* Yanlin Wu,2,* Hongxuan Tong3,4 1Stomatology Grade 2022, School of Clinical Medicine, Hangzhou Normal University, Hangzhou, 311121, People’s Republic of China; 2Clinical Medicine Grade 2021, School of Clinical Medicine, Hangzhou Normal University, Hangzhou, 311121, People’s Republic of China; 3Academy of Chinese Medical Sciences, Beijing, People’s Republic of China; 4Institute of Basic Theory for Chinese Medicine, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongxuan Tong, Institute of Basic Theory for Chinese Medicine, China, No. 16, Dongzhimen Inner South Street, Beijing, People’s Republic of China, Email thongxuan1@163.com